EFFECT OF RAINFALL VARIABILITY ON THE SUSTAINABILITY OF GINGER YIELD IN JABA LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Atiyong, B. R.; Abaje, I. B.; Abdulkarim, B. (FUDMA Journal of Sciences, 2023)
This study examined the effects of rainfall variability on the sustainability of ginger yield in Jaba Local Government Area of Kaduna State. Rainfall data for 15 years (2001 to 2015) was analyzed in order to establish the pattern of rainfall anomalies in the area. 274 copies of questionnaires were purposively administered to farmers in order to examine their perception on the effects of rainfall variability on ginger yield in the study area. Linear regression was used to determine the linear trends of rainfall and ginger yield, the Standardized Anomaly Index was then used to determine the dry (-ve values) and wet (+ve values) years in the rainfall series. The relationship between rainfall and ginger yield was determined using Pearson’s product moment correlation coefficient, while the perceptions of farmers on the effects of rainfall variation on ginger yield was analyzed using descriptive statistics. The study revealed that as the rainfall is increasing, so also is ginger yield increasing. The Standardized Anomaly Index revealed positive and negative anomalies within the period. The study further observed that fluctuation of rainfall does not have an adverse effect on sustainability of ginger yields. The results of the correlation analysis between the annual rainfall amount and ginger yield showed a strong positive monotonic relationship (r= 0.61) between ginger yield and rainfall amount. The study recommends the need for extension agents to sensitize farmers on adjustments of farming calendar to synchronize planting and growing period. Agricultural Research Institutes in the country should develop drought resistant and early.
Keywords: Anomalies, climate change, communities, farmers, Onset